Stress levels among pre-clinical Medical students and their coping strategies - Muhammad Hasnat Akhtar; Anum Ashfaq; Ahmed Murtaz Khalid; Mukhtiar Baig (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Stress is no doubt prevalent among medical students. Insight into how different personality types cope with this challenge might give the opportunity to healthcare authorities to devise a more standardized guideline for conducting a psychological aptitude test at the time of intake into medical school. Our objective is to look at the stress and anxiety among medical students and how different personality types cope with stress.METHODOLOGY: A Cross-sectional descriptive study was carried out at CMH Kharian Medical College from November 2020 to May 2021. Agha Khan University, Anxiety and Depression Scale was employed to assess stress and anxiety levels among medical students. Myers–Briggs Type Indicator (MBTI) was used to identify personality traits, and the “Brief COPE Inventory Scale” was employed to investigate stress coping styles(approach or avoidant) among students. SPSS was used to analyze the results.RESULTS: Out of 158 participants, 108(68.4%) were females, and 50(31.6%) were males. More than half of the preclinical medical students, 93(58.86%) were having stress [females 73(67.59%), males 20(40%)]. Personality types showed that 100(63.3%) students belonged to the introvert group, while 58(36.7%) students belonged to the extrovert group. Most participants, 144(91%) students, adopted approach coping styles rather than avoidant ones (14 (8.86%). Stress was significantly associated with personality types (p=0.021), coping style (p=0.007), and gender (female) (p=0.001). However, we did not find any association between personality types & coping styles (p=0.936).CONCLUSION: High level of stress and anxiety (58.86%) was found among students and was more prevalent among females and extroverted medical students. Both personality types (extroverts and introverts) used approach coping styles rather than avoidant trends.